The dawn of everything : a new history of humanity - Graeber, David; Wengrow, D. (New York : Farrar, Straus and Giroux, 2021)
"A trailblazing account of human history, challenging our most fundamental assumptions about social evolution-from the development of agriculture and cities to the emergence of "the state," political violence, and social inequality-and revealing new possibilities for human emancipation"--
Farewell to humanity's childhood, Or, why this is not a book about the origins of inequality -- Wicked liberty : The indigenous critique and the myth of progress -- Unfreezing the Ice Age : In and out of chains : the protean possibilities of human politics -- Free people, the origin of cultures, and the advent of private property (not necessarily in that order) -- Many seasons ago : Why Canadian foragers kept slaves and their Californian neighbours didn't ; or, the problem with 'modes of production' -- Gardens of Adonis : The revolution that never happened : how Neolithic peoples avoided agriculture -- The ecology of freedom : How farming first hopped, stumbled and bluffed its way around the world -- Imaginary cities : Eurasia's first urbanites - in Mesopotamia, the Indus Valley, Ukraine and China - and how they built cities without kings -- Hiding in plain sight : The indigenous origins of public housing and democracy in the Americas -- Why the state has no origin : The humble beginnings of sovereignty, bureaucracy, and politics -- Full circle : On the historical foundations of the indigenous critique -- The dawn of everything.
Includes bibliographical references (pages 611-673) and index.
Keywords: World history